Salmoneloses emergentes de origem aviária - Kowalski, Luciana Helena; Fernandes, Sergio Rodrigo; Silva, Ana Paula; Bredt, Raquel Cristina; Cruz, Thiago Augusto; Silva, Marina Gabriela Berchiol da [UNESP] (My University, 2011)
The genus Salmonella are rod-shaped facultative anaerobes enterobacteria that are obligatory intracellular parasites and worldwide distributed. These pathogens are considered of great importance for animals as for humans. In broiler industry, Salmonella normally cause no harm to poultry, but are involved in foodborne diseases in humans and represent a significant public health problem. The main source of transmission to humans is the consumption of eggs, followed by bovine meat and chicken. Control of this disease is complex because of its wide distribution, making it necessary to adopt preventive measures, because once present in the production chain of poultry industry, the health management for control of Salmonella is expensive. In general, clinical signs of salmonellosis are associated with the gastrointestinal tract, but systematic infection can occur with death. The losses are high for both poultry industry and for public health, and the best way to reduce costs are related to the disease is by adopting preventive measures rather than curative measures. The objective of this review is to show the importance of avian Salmonella in public health.

As bactérias do gênero Salmonella sp. são bastonetes da família Enterobacteriaciae, anaeróbios facultativos e parasitas intracelulares facultativos com distribuição cosmopolita. São considerados patógenos de grande importância tanto para animais como para humanos. Na indústria avícola, as salmonelas geralmente não causam enfermidades nas aves, porém estão envolvidas em toxinfecções alimentares em humanos e são consideradas de grande importância para saúde pública. A principal fonte de transmissão para humanos é o consumo de ovos, seguido da carne de frango. O controle desta doença é complexo devido a sua ampla distribuição, tornando-se necessário a adoção de medidas preventivas, pois uma vez presente na cadeia de produção da indústria avícola, o manejo sanitário para controle da Salmonella sp. é oneroso. Em geral os sinais clínicos da salmonelose estão associados ao trato gastrointestinal, porém pode ocorrer infecção sistêmica com casos de morte. Os prejuízos são elevados tanto para a indústria avícola quanto para a saúde pública, sendo que a melhor forma de reduzir os gastos relacionados à enfermidade é adotando medidas preventivas e não curativas. O objetivo desta revisão é mostrar a importância da salmonelose de origem aviária na saúde pública.
Emergent salmonellosis of avian origin
Keywords: Poultry industry; Salmonella sp.; Public health; Foodborne disease; Indústria avícola; Salmonella sp.; Saúde pública; Toxinfecções alimentares